Chapter Mari connessi - North, Michael (Atti delle «Settimane di Studi» e altri Convegni, 2019)
Following Fernand Braudel's Méditerranée, historians interpreted the Mediterranean, Baltic, Atlantic, Indian Ocean or Pacific as closed maritime systems, consisting of multiple micro-environments. This essay seeks to overcome these limited perspectives and to examine, how the various seas and oceans were connected by the Vikings, the Cairo Genizah merchants and the Italian trading companies of the Middle Ages. The second part of my article "Connected Seas" examines the perception and memory of the seas as an element of maritime connectivity. It introduces the concept of realm of memory (lieu de mémoire) into maritime history and tests it in four case studies on the Sound, the Straits of Gibraltar, the Dardanelles and the Straits of Malacca.